Small vessel disease and biomarkers of endothelial dysfunction after ischaemic stroke. (June 2019) - Arba, Francesco; Giannini, Alessio; Piccardi, Benedetta; Biagini, Silvia; Palumbo, Vanessa; Giusti, Betti; Nencini, Patrizia; Maria Gori, Anna; Nesi, Mascia; Pracucci, Giovanni; Bono, Giorgio; Bovi, Paolo; et al.
Abstract: Introduction: Although pathogenesis of small vessel disease is poorly understood, increasing evidence suggests that endothelial dysfunction may have a relevant role in development and progression of small vessel disease. In this cross-sectional study, we investigated the associations between imaging signs of small vessel disease and blood biomarkers of endothelial dysfunction at two different time points in a population of ischaemic stroke patients. Patients and methods: In stroke patients treated with intravenous thrombolysis, we analysed blood levels of von Willebrand factor, intercellular adhesion molecule-1, vascular cell adhesion molecule-1 and vascular endothelial growth factor. Three reviewers independently assessed small vessel disease features using computed tomography. At baseline and 90 days after the index stroke, we tested the associations between single and combined small vessel disease features and levels of blood biomarkers using linear regression analysis adjusting for age, sex, hypertension, diabetes, smoke. Results: A total of 263 patients were available for the analysis. Mean age (±SD) was 69 (±13) years, 154 (59%) patients were male. We did not find any relation between small vessel disease and endothelial dysfunction at baseline. At 90 days, leukoaraiosis was independently associated with intercellular adhesion molecule-1 (β = 0.21; p = 0.016) and vascular cell adhesion molecule-1 (β = 0.22; p = 0.009), and lacunes were associated with vascular endothelial growth factor levels (β = 0.21; p = 0.009) whereas global small vessel disease burden was associated with vascular endothelial growth factor (β = 0.26; p = 0.006). Discussion: Leukoaraiosis and lacunes were associated with endothelial dysfunction, which could play a key role in pathogenesis of small vessel disease. Conclusions: Small vessel disease features and total burden were associated with endothelial dysfunction 90 days after the stroke, whereas there was no relation during the acute phase. Our results suggest that endothelial dysfunction, particularly vascular endothelial growth factor, is involved in pathological process of small vessel disease.